Social Media Marketing pada UMKM dengan Memanfaatkan E-Commerce : (Studi pada 3 UMKM di Tangerang Selatan) - Achmad Shidqi Pratama Buana Firdaus; Aminah Swarnawati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Social media marketing is a form of marketing using social media that utilizes target markets that participate as social media users. Currently, many MSMEs use social media marketing by using e-commerce as a liaison between sellers and buyers. Based on this, the purpose of this study is to describe social media marketing for MSMEs that use e-commerce and the advantages of social media in promoting products carried out by MSMEs. Using the Gunelius 2011 theory, namely Social Media Marketing which includes indicators of Content Creation, Content Sharing, Connecting, Community Building. The approach to this study is qualitative with descriptive methods. The data collection techniques used are interviews and observations. Overall, the results obtained in this study indicate that social media marketing provides easy access to using social media as a means of promoting a product, by making content as attractive as possible, it can provide more interest in consumers for products distributed through social media, in other words, the distribution of content also provides a sense of awareness to consumers for the products offered, coupled with the existence of e-commerce that can provide reviews and reviews of products purchased, providing support for MSMEs who use social media as a means of promotion. By making connections and building communities, it also provides WOM to MSME actors and there is an exchange of ideas between MSME actors and consumers.